2023
DOI: 10.2471/blt.22.288703
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and perinatal death surveillance and response: a systematic review of qualitative studies

Abstract: Objective To understand the experiences and perceptions of people implementing maternal and/or perinatal death surveillance and response in low- and middle-income countries, and the mechanisms by which this process can achieve its intended outcomes. Methods In June 2022, we systematically searched seven databases for qualitative studies of stakeholders implementing maternal and/or perinatal death surveillance and response in low- and middle-income countries. Two reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Challenges in conducting MDR revealed poor validity for data collection which raises questions not only about the feasibility of the MDR's tool but also about the form used to collect data, data collector skills, the stakehoders at facilities awareness of maternal death, and the reviewer's objectivity (12,13,30). Several studies reported how the inadequate information to support evidence-based policy-making results in unreliable identi cation of the underlying cause of maternal death in the review (10,14). In our discussion of validity in formulating evidence-based recommendations, the analyzing of information surrounding maternal death has be supported by the ow of evidence used as reference to conduct the review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Challenges in conducting MDR revealed poor validity for data collection which raises questions not only about the feasibility of the MDR's tool but also about the form used to collect data, data collector skills, the stakehoders at facilities awareness of maternal death, and the reviewer's objectivity (12,13,30). Several studies reported how the inadequate information to support evidence-based policy-making results in unreliable identi cation of the underlying cause of maternal death in the review (10,14). In our discussion of validity in formulating evidence-based recommendations, the analyzing of information surrounding maternal death has be supported by the ow of evidence used as reference to conduct the review.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies reported that ensuring the compliance of health care facilities to collect reliable data remains a major challenge associated with unfavorable institutional cultural attitudes called 'blame culture'. Instead of engaging in a productive action cycle, this unfavorable culture causes a 'vicious circle' involving reluctance to provide the con dential information related to the chronological events involved in maternal death, subjectivity in maternal case analysis, and poor feedback for quality improvement (10,11,13,14). Our more recent study called for explicit clinical standards for MDR to prevent the 'punitive actions' commonly attributed to the lower-level facilities and reluctance to identify de ciencies of care provided by senior colleagues (15).…”
Section: Introductionmentioning
confidence: 99%
“…Successful MDSR implementation can be expected to lead to improved quality of care and reduced maternal mortality. As noted by Willcox and colleagues 11 "the key context to enable effective death surveillance and response was a blamefree learning environment with good leadership." The politicization of maternal death reviews and the fear of punitive actions and litigations, as reported from Ethiopia, 4,5 can be demotivating and lead to "a vicious cycle of under-reporting, inaccurate data, and inadequate review and recommendations, which lead to demotivation and disengagement."…”
Section: Establishing Mdsr Takes Timementioning
confidence: 99%
“…Health workers oriented to the maternal and perinatal deaths surveillance and response systemare believed to be able to identify health-related actions that may contribute to the prevention of further maternal and perinatal deaths timely [14]. Nevertheless, health workers who are empowered adequately on the maternal and perinatal deaths surveillance and response system are therefore expected to demonstrate competencies in assigning appropriate and timely health-related actions to particular groups or individuals, designatingtime frames for accomplishing the actions,and following up their implementations and effectiveness about pregnant mother's response to care [15].…”
Section: Introductionmentioning
confidence: 99%